KESESUAIAN KOMPETENSI PERAWAT GIGI DENGAN POLA ASUHAN KEPERAWATAN GIGI ANAK DI PUSKESMAS WILAYAH KOTA YOGYAKARTA - , UMI MA RIFAH NIHAYATI, Prof. Dr. drg. Iwa Sutardjo RS, SU.,Sp.KGA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dental nurse is a person who has attended and graduated from dental nurse education recognized by the government. In order to provide the best health service, it is necessary to avoid overlapping roles and quality gaps, dental nurse in performing their profession used competency guidance, though the obedience towards it was based on their own behavior. Pattern of pediatric dental care is an interaction between patient and dental nurse which there is one model or structure become an example in parenting. This study aims to know how is the pattern of pediatric dental care in Community Health Center around Yogyakarta region. This qualitative descriptive study had been done to 44 subjects of dental nurses in Community Health Center around Yogyakarta region using observational method. Collecting data done through interview and questioner filling about dental nursesâ main capability later analyzed using frequency distributive test and presented descriptively. The result showed there were 4 from 8 indicators of dental nursesâ capability did not qualify with the standards of Ministry of Health Republic of Indonesia Number 378/Menkes/SK/III/2007. By 77,3% of dental nurses pursuing one way communication. Extraction of permanent teeth with a single root using infiltration anesthesia without any supervision in pediatric patient carried out by 97,7% of dental nurses. By 81,8% of dental nurses done cavity preparation and one to two surface primary or permanent restoration without supervision. Trepanation treatment in pediatric patient done by 93,2% of dental nurses without supervision. In conclusion of the pattern of pediatric dental care in Community Health Center around Yogyakarta region, 50% of the indicators of dental nursesâ capability were a well done and were suitable with the standards of Ministry of Health Republic of Indonesia while half of the rest were not suitable yet.